2005
DOI: 10.1039/b505493a
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmotic flow analysis of a branched U-turn nanofluidic device

Abstract: In this paper, we present the analysis of electroosmotic flow in a branched U-turn nanofluidic device, which we developed for detection and sorting of single molecules. The device, where the channel depth is only 150 nm, is designed to optically detect fluorescence from a volume as small as 270 attolitres (al) with a common wide-field fluorescent setup. We use distilled water as the liquid, in which we dilute 110 nm fluorescent beads employed as tracer-particles. Quantitative imaging is used to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…12 We therefore focus our observations in this study on the same region, which is also shown as the red rectangle in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We therefore focus our observations in this study on the same region, which is also shown as the red rectangle in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…However, in channels with a low Reynolds number ͑in our case: in the order of 10 −3 ͒, these inertia forces become negligibly small, such that particles and molecules can turn around sharp corners without exhibiting a significant momentum. 12 Therefore, after considering all the forces above, it is valid for us to assume that the observed size-dependent trajectories in our experiments are solely due to dielectrophoresis. Nevertheless, the discussion above highlights how complex the physical system in the experiment is, such that the list of forces we provided above might be not entirely complete.…”
Section: Physical Mechanism Of Confined Dna Dielectrophoresismentioning
confidence: 99%
“…Sikanen et al 2005 determined the f-potential via a conductivity increase of the fluid between sample and waste reservoir, at which a higher buffer concentration displaced the lower one by EOF of the fluid and electrophoretic migration of the buffer molecules. Other methods observe the absolute velocity of the carrier fluid with microbeads (Parikesit et al 2005;Lee et al 2004). Nonnegligible electrophoretic mobilities and nonspecific charging of the microbeads during the measurement causes a measurement error.…”
Section: Measurement and Evaluationmentioning
confidence: 98%
“…28,32 While studies of particles are limited, measurements of the polarizability of biomolecules have proceeded over the past decades and have resulted in approaches that could potentially provide measurements of polarizability of abiotic nanoscale objects. [33][34][35][36][37][38][39][40][41][42][43][44][45] However, measurements of DNA and other biomolecules have revealed puzzling behavior regarding the interaction between salt concentration and polarizability that has not yet been reconciled, likely due to the difficulty in accurately modeling biomolecules as simple structures. 42,44,46,47 Here, we develop a method to measure the polarizability of photoluminescent nanoparticles and use it to quantify the polarizability of semiconductor quantum dots (QDs), which is found to dramatically increase at low salt concentrations (Figure 1B).…”
mentioning
confidence: 99%
“…6-10, 13, 14, 48 This, together with individual particles being optically resolvable, enables indirect quantification of α through measurements of velocity resulting from a competition between drag and DEP, 6,11,13,15 the external flow speed needed to dislodge a particle from a stationary DEP trap, 7,39 or the trajectory of particles through curving fluid flows. 41 In interpreting such measurements, material properties are typically estimated using analytical models such as the expression for a spherical particle,…”
mentioning
confidence: 99%